Construction of hybrid g-C3N4/CdO nanocomposite with improved photodegradation activity of RhB dye under visible light irradiation - Thurga Devi, Munusamy; Chin, S. Y.; Khan, Maksudur R. (Elsevier Ltd, 2020)
The hybrid graphitic carbon nitride-cadmium oxide (g-C3N4/CdO) nanocomposite was fabricated using chemical precipitation and self-assembly method. The photocatalysts were characterised by XRD, XPS, FTIR, BET, TEM, FESEM, UV-Vis and PL spectroscopy. Based on the optical study, visible light harvesting was improved and the band gap of bulk g-C3N4 to hybrid g-C3N4/CdO nanocomposite was greatly reduced from 2.72 eV to 2.35 eV, signifying a better charge carrier mobility. The photocatalytic activity were further assessed by conducting rhodamine B (RhB) photodegradation reaction using visible light. An excellent dye removal efficiency of 96% was achieved when 1.5 g/L of hybrid g-C3N4/CdO nanocomposite was used with an initial concentration of 10 ppm for 120 min whereas only 66% of RhB was removed by bulk g-C3N4 within the same operating conditions. Besides, reusability tests were carried out and evidenced that hybrid g-C3N4/CdO nanocomposite can be recycled up to four times by retaining the degradation efficiency. The scavenging studies confirmed that the RhB photodegradation using hybrid g-C3N4/CdO nanocomposite was controlled by valance band h+ and O2− oxidation reactions. Conclusively, the inclusion of CdO onto g-C3N4 resulted in remarkable photocatalytic activity for dye degradation applications.